Microbiological surveillance post-reprocessing of flexible endoscopes used in digestive endoscopy: a national study. (January 2023) - Casini, B.; Spagnolo, A.M.; Sartini, M.; Tuvo, B.; Scarpaci, M.; Barchitta, M.; Pan, A.; Agodi, A.; Cristina, M.L.; ,; Baroncelli, L.; Castiglia, P.; et al.
Summary: Introduction: Microbiological surveillance of endoscopes is a safety measure for verifying the quality of reprocessing procedures and identifying contaminated devices, but duodenoscope-related outbreaks are still reported. Aim: To assess the effectiveness of duodenoscope reprocessing procedures in Italy. Methods: Between December 2019 and April 2020, data obtained from microbiological surveillance post-reprocessing in 15 Italian endoscopy units were collected. Sampling was carried out after reprocessing or during storage in a cabinet. In keeping with international guidelines and the Italian position paper, the micro-organisms were classified as high-concern organisms (HCOs) and low-concern organisms (LCOs). Findings: In total, 144 samples were collected from 51 duodenoscopes. Of these, 36.81% were contaminated: 22.92% were contaminated with HCOs and 13.89% were contaminated with LCOs [2.08% with an LCO load of 11–100 colony-forming units (CFU)/device and 0.69% with an LCO load of >100 CFU/device]. The contamination rate was 27.5% in samples collected after reprocessing, 40% in samples collected during storage in a cabinet that was compliant with EN 16442:2015 (C-I), and 100% in samples collected during storage in a cabinet that was not compliant with EN 16442:2015 (NC-I). The respective HCO rates were 15.00%, 27.27% and 66.67%. Correlation between LCO contamination and storage time was demonstrated (Spearman's rho=0.3701; P =0.0026). The Olympus duodenoscope TJFQ180V demonstrated the lowest rate of contamination (29.82%), although the contamination rate was 100% for duodenoscopes stored in an NC-I cabinet. Conclusion: Microbiological surveillance, along with strict adherence to reprocessing protocols, may help to detect endoscope contamination at an early stage, and reduce the risk of duodenoscope-associated infections.